Alat Bantu Jalan Sensorik bagi Tunanetra - Kurniawan, Asep (PLD UIN Sunan Kalijaga, 2019)
The existing mobility aids for the visually impaired today still have several shortcomings, so it is necessary to develop technology that can help them walk better. This study aims to create a walker with sensors that can move right and left. Research also tests its accuracy, precision, and success. In making the tool, two steps are taken: making tools and testing tools. The device consisted of an HC-SR04 ultrasonic sensor, two Arduino Nano, an SG90 servo motor, and a buzzer. The product then was tested by reading distances at variations of 60cm, 70cm, 80cm, 90cm and 100cm. In addition to distance testing, the instrument is also tested at 0 °, 30 ° right and left angles and 60 ° right and left — output device in the form of a buzzer sound. This design of mobility aids for the blind people have an accuracy of 99.995% and a precision (repeatability) of 98.600%. Meanwhile, this tool has a percentage of the success rate of 98,400%.[Alat bantu jalan bagi tunanetra saat ini masih memiliki kekurangan sehingga diperlukan pengembangan teknologi yang dapat membantu mereka berjalan. Penelitian ini bertujuan untuk membuat alat bantu jalan dengan sensor yang dapat bergerak ke kanan dan ke kiri serta menguji akurasi, presisi, dan tingkat keberhasilan alat. Penelitian dilakukan dalam dua tahap yaitu membuat alat dan menguji alat. Alat dibuat menggunakan sebuah sensor ultrasonik HC-SR04, dua buah arduino nano, sebuah motor servo SG90, dan sebuah buzzer. Alat diuji dengan membaca jarak pada variasi 60cm, 70cm, 80cm, 90cm, dan 100cm. Selain pengujian jarak, alat juga diuji pada sudut 0°, 30° kanan dan kiri serta 60° kanan dan kiri. Output alat berupa bunyi buzzer. Hasil penelitian rancang bangun alat bantu jalan bagi penyandang tunanetra yang telah dibuat memiliki akurasi 99,995% dan presisi (repeatability) sebesar 98,600%. Adapun, alat ini memiliki persentase tingkat keberhasilan sebesar 98,400 %.]